Weighted frequency hopping control in TDL for coexistence of satellite spectrum - Choi, Seonjoo; Lim, Jaesung; Baek, Hoki (International Conference on Information Networking, 2018)
Recently, the concept of modern operations is changing from the platform-centric warfare to the network-centric warfare (NCW). In the NCW, situational awareness through tactical information sharing among all network participants is very important. Tactical data links(TDLs) are important systems for real-time tactical information distribution and command and control capabilities in the network-centric warfare. If the TDL employs frequency hopping technique for providing anti-jamming and multi-net capabilities, then it requires large bandwidth. In order to resolve the spectrum allocation problem, the previous study considered spectrum sharing with the fixed satellite services (FSS) and proposed the weighted frequency hopping (WFH) scheme to reduce pulse collision probability. However, the study did not provide how the weight parameter is determined, even if the multi-net performance is dependent on it. Therefore, in this paper, we provide a weight control method to find the weight parameter that approximately maximizes the performance. In addition, we provide a new performance metric, message error rate (MER), to show multi-net performance. The simulation results show that weights should be used differently depending on how much the satellite is using the resource.
Keywords: Link-16; Multi-net; Satellite communications; Spectrum sharing; Tactical data links; Frequency hopping; Link-16; Multi-net; Satellite-communication; Spectrum sharing; Tactical data link